2015
DOI: 10.4102/curationis.v38i2.1535
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of contraceptives by female undergraduate students in a selected higher educational institution in Gauteng

Abstract: BackgroundUnplanned pregnancies amongst students at higher education institutions are a major concern worldwide, including South Africa. Apart from various social and psychological challenges, unplanned pregnancies affect students’ objectives of achieving academic success. Research undertaken in the United States of America (USA) indicates that around 80% of female students in institutions of higher education between ages 18 and 24 are sexually active.ObjectivesTo assess and describe the use of contraceptives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 14 publications
2
30
0
2
Order By: Relevance
“…In a study by Coetzee and Ngunyulu 16 comprising 400 female undergraduate students at a Gauteng tertiary institution, 74% of participants were sexually active, of whom 79% used contraception: oral contraceptives were preferred by 38% and male condoms by 25%. An earlier study by Oyedeji and Cassimjee 17 among university students at KwaZulu-Natal showed a preference for male condom use among unmarried female students due to the stigma of using pills or visiting the clinic for injections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Coetzee and Ngunyulu 16 comprising 400 female undergraduate students at a Gauteng tertiary institution, 74% of participants were sexually active, of whom 79% used contraception: oral contraceptives were preferred by 38% and male condoms by 25%. An earlier study by Oyedeji and Cassimjee 17 among university students at KwaZulu-Natal showed a preference for male condom use among unmarried female students due to the stigma of using pills or visiting the clinic for injections.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Coetzee and Ngunyulu 16 done in Gauteng found that 53.3% of female undergraduate students were familiar with emergency contraception. Similar results were reported by Hoque and Ghuman 21 for female university students in KwaZulu-Natal where 49.8% of students had heard of emergency contraception and 21.2% of sexually experienced students had used emergency contraception.…”
Section: Knowledge Of Hormonal Contraceptionmentioning
confidence: 99%
“…Throughout the world, female students are exposed to the risk of unplanned pregnancies as a result of ineffective or non-use of contraceptives (Tsui et al, 2010). This may result in failure to complete their education, inability to maintain gainful employment as well as making independent marital decisions (Coetzee and Ngunyulu, 2015). Young students' sexual activities are a communal, municipal and public health concern.…”
mentioning
confidence: 99%
“…times more likely to have an induced abortion than less educated youth, which contributes to potential maternal morbidity in the context of restrictive laws on abortion (Menezes, Aquino, 2009). High rates of contraceptive discontinuation resulting in unintended pregnancies amongst students at higher education institutions are also reported in other countries, including Asia, Africa, and the U.S. (Trieu et al, 2011;Mehra et al, 2012;Somba et al, 2014;Coetzee, Ngunyulu, 2015;Wang et al, 2015).…”
Section: Special Needs Of University Studentsmentioning
confidence: 86%
“…including Brazil, falls on youth (ages 15 to 24) who are at the peak of their fertile years (Berquó, Lima, 2008;IBGE, 2010;Diamond-Smith, Moreau, Bishai, 2014;Wellings et al, 2015;Coetzee, Ngunyulu, 2015;Finer, 2016;Moreau, Bohet, 2016).…”
Section: Introductionmentioning
confidence: 99%